ANALISIS HUBUNGAN KEBIJAKAN PUBLIK TENTANG PEMANFAATAN DANA ALOKASI CUKAI DENGAN PERMINTAAN ROKOK DI KABUPATEN SUMENEP - - Junaidi (Trunojoyo University of Madura, 2011)
The objectives of this research were to examine people perception in the increase of tobacco tax in relation to cigarette price, the rule limiting smoking area, and the campaign of smoking impacts to the health with cigarette demand that may cause the reduce in tobacco demand. The research was carried out in Sumenep Regency from March 2009 to October 2009. A randomly sampling method based on area was employed to determine the sample in order to collect data. The results showed that there were significant correlation between the campaign of cigarette band and its demand. The size of cigarette factory own by community had positive correlation with tobacco demand.